Technical education and other essays : viz., the biological sciences and medicine ; Joseph Priestley ; Sensation and the sensiferous organs ; Certain errors attributed to Aristotle / by Thomas H. Huxley. - Huxley, Thomas Henry, 1825-1895. (Tufts University. Tisch Library., 2015)
1 online resource (50 pages) : illustrations.; "March, 1885."; Double paging. Pages also numbered as part of a larger resource: 336-384.; Caption title.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Series: Humboldt library ; no. 66.